2017
DOI: 10.1093/pm/pnx087
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transcranial Direct Current Stimulation of the Motor Cortex on Visceral Pain in Patients with Hepatocellular Carcinoma

Abstract: tDCS proved to be an effective and clinically relevant therapeutic strategy for visceral pain due to HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(58 citation statements)
references
References 60 publications
1
55
0
2
Order By: Relevance
“…[16] Eventually, a total of 6 studies were identified which complied with the overall criteria. [1722]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[16] Eventually, a total of 6 studies were identified which complied with the overall criteria. [1722]…”
Section: Resultsmentioning
confidence: 99%
“…The main treatment and study characteristics as well as the quality criteria of the 6 RCT's [1722] are summarized in Tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, contemporary data demonstrate that adverse structural and functional changes in the peripheral and central nervous systems may cause patients experiencing chronic abdominal pain to suffer increased pain perception. 11 Peripheral inflammation and recurrent acute pain contribute to visceral hypersensitivity. At the level of the central nervous system, recurrent acute pain contributes to hyperexcitability in pain-associated brain areas by creating synaptic connections and strengthening existing connections.…”
Section: Pain Classificationsmentioning
confidence: 99%
“… 24 Transcranial direct current stimulation (tDCS) may prove an effective therapy to alleviate visceral HCC pain. 11 Multiple sessions of tDCS over the primary motor cortex generated analgesic responses in HCC patients experiencing visceral pain, where relief appeared by the fifth session and persisted for a month. This method may be especially promising because it carries negligible risk and device application is simple.…”
Section: Pain Management and Associated Challengesmentioning
confidence: 99%
See 1 more Smart Citation